Melasma: A clinicopathological study of 43 cases - Sarvjot Vermani; Sharma Shruti; Mishra Sharmila; Singh Avninder (Wolters Kluwer Medknow Publications, 2009)
Melasma is a symmetrical hypermelanosis of the exposed skin characterized by brown macules on the sun-exposed areas of the skin. The present study was carried out on 43 patients to analyze the correlation between histopathological features with clinical and Wood′s light examination. The study showed a clinical and histopathological discordance of 16.2%. Solar elastosis (55.8%) was the single most common histological finding apart from increased melanin concentration, epidermal flattening and dermal lymphomononuclear inflammation.